Understanding the methodologies of the four sunni mazhabs - Hanapi, Nureen Hafiza; Mohd Salehudin, Mardiyyah Mutmainnah; Bakri, Husna Najihah; Abdul Hamid @ Sulaiman, Nur Aina Adlina; Amram, Adriana Izzah (2025)
This study aims to gain an in-depth understanding of the methodologies used by the four main schools of Sunni Islam, Hanafi, Maliki, Syafi‘i and Hanbali, in formulating and issuing sharia law. Although all schools adhere to the same basic sources, namely the Qur’an and Sunnah, differences in approach, historical background and principles of ijtihad have created various methodologies that are valid and accepted within the framework of Ahli Sunnah Wal Jamaah. This study uses a qualitative method based on content analysis and literature review of classical and contemporary works in the field of fiqh and usul fiqh. The focus of the study includes the sources of law recognized by each school, methods of legal inference such as qiyas, istihsan, maslahah and ‘urf, as well as a comparison between the respective methodological approaches. This study also analyses how these inherited methodologies are applied in contemporary contexts to resolve various current issues such as ethics, Islamic finance and modern technology. The results of the study show that each school has a methodological framework that is structured, flexible and able to interact with the times without compromising the principles of sharia. Understanding this methodology not only strengthens the discourse of comparative jurisprudence but also helps contemporary Muslim society to choose legal views in a more informed and responsible manner.